The Effects of Word Of Mouth on Movies & Its Impact on the Audience's Choice - Dodhia, Shreya (2008)
Consumers discuss products and services and their experiences with others and thus become indirect marketers. The only difference is that this marketing may not always be in the favour of the product/service. Thus, marketers need to learn how to use this method to their benefit, and this is only possible through thorough knowledge, practice and patience. Therefore, this study aims to highlight the concepts of word-of-mouth, in the context of services, in order to help marketers better understand the elements and characteristics as well as the influences of word-of-mouth on consumers' decision making process. This is done through the reviewing of literature which not only reveals the theory of word-of-mouth, but also taps onto the reasons as to why people share comments and experiences as well as why people listen to these. It also helped to develop a framework which was used as the base of the study. As a result of the framework, this study explores the impact of the audience's choice on the success of motion pictures/movies as a consequence of word-of-mouth. The research employed shows that viewers search for movie related information before making their purchase and highlights the factors that most influence their choice. It also enlightens on the fact that strong ties are important elements of the social network and their influence on one's choice is powerful. Furthermore, the types of word-of-mouth: negative and positive, affect the decision of the audience and thus have an overall impact on the income for the film in terms of the audience's attendance/box office returns. Overall, it supported the developed framework.